Clinical features of children with chronic non-bacterial osteomyelitis: A multicenter retrospective case series from Turkey - Ceyhun Açarı,; Elif Çomak,; Şükrü Çekiç,; Serkan Türkuçar,; Hatice Adıgüzel Dündar,; Sara Şebnem Kılıç,; Sema Akman,; Balahan Makay,; Şevket Erbil Ünsal, (Archives of Rheumatology, 2021)
Objectives: This study aims to evaluate demographic, clinical, and radiological characteristics of Turkish children with chronic non-bacterial osteomyelitis. Patients and methods: Between January 2008 and December 2018, a total of 28 patients (10 males, 18 females; median age: 12.5 years; range, 4.5 to 21 years) who were diagnosed with chronic non-bacterial osteomyelitis in three pediatric rheumatology centers were retrospectively analyzed. The demographic, clinical, and laboratory findings of the patients were recorded. Results: The median age at the time of diagnosis was 10.2 years. The median time from symptom onset to diagnosis was 6.5 months. The median follow-up was 18.5 months. The most frequent symptom at onset was arthralgia (75.0%). The most frequently involved bone was the femur (67.9%). Eight (63.6%) of 12 patients had at least one Mediterranean fever gene (MEFV) mutation, indicating a significantly higher prevalence than the Turkish population (14.8%). Five of these patients fulfilled the diagnostic criteria for familial Mediterranean fever (FMF). All patients received non-steroidal anti-inflammatory drugs. Other drugs were methotrexate (46.4%), sulfasalazine (39%), corticosteroids (25%), anti-tumor necrosis factor (anti-TNF) agents (32%), pamidronate (25%), and colchicine (21.4%). Six of eight patients with MEFV mutations were administered with colchicine, and all of them responded to treatment. Conclusion: Clinical evolution and imaging investigations should be carefully performed to prevent any delay in the diagnosis of patients with chronic non-bacterial osteomyelitis. Based on our study results, FMF coexistence is worth investigating in patients with chronic non-bacterial osteomyelitis, particularly in the Turkish population.